Mandibular Bone and Soft Tissues Necrosis Caused by an Arsenical Endodontic Preparation Treated with Piezoelectric Device - A. Giudice; M. G. Cristofaro; I. Barca; D. Novembre; M. Giudice (Case Reports in Dentistry)
This paper describes a case of wide mandibular bone necrosis associated with significant soft tissues injury after using an arsenical endodontic preparation in the right lower second molar for endodontic purpose. Authors debate about the hazardous effects of the arsenic paste and the usefulness of piezosurgery for treatment of this drug related bone necrosis.